TINJAUAN MARKETING SYARI’AH TERHADAP SISTEM PERDAGANGAN KULINER ONLINE MASA PANDEMI COVID-19 DI DESA GEDANGAN MOJOWARNO JOMBANG - Nurul Imamah, Mutia Izzatun; Asi Islami, Trinah (Irtifaq, 2023)
This article aims to find out how the online culinary trading system was during the Covid-19 pandemic in Gedangan Hamlet, Mojowarno District, Jombang Regency as well as sharia marketing knowledge of the online culinary trade practice. Using a qualitative method that will produce descriptive data in the form of written words, using an empirical juridical approach that takes data sources through direct observation and also library data sources. The results showed that the trading system that occurred in Gedangan Hamlet, Gedangan Village was in accordance with the existing trading system, and according to sharia marketing the owner in marketing a product did not meet the characteristics of sharia marketing. Suggestions for online culinary traders to be more open to fellow traders and support each other and promote each other's products.